Rumen-protected zinc–methionine dietary inclusion alters dairy cow performances, and oxidative and inflammatory status under long-term environmental heat stress - Danesh Mesgaran, Mohsen; Kargar, Hassan; Janssen, Rieke; Danesh Mesgaran, Sadjad; Ghesmati, Aghil; Vatankhah, Amirmansour (Frontiers in Veterinary Science, 2022)
Dairy cows are susceptible to heat stress due to the levels of milk production and feed intake. Dietary supplemental amino acids, particularly rate-limiting amino acids, for example, methionine (Met), may alleviate the potential negative consequences. Zinc (Zn) is beneficial to the immune system and mammary gland development during heat stress. We investigated the impact of a source of a rumen-protected Zn-Met complex (Loprotin, Kaesler Nutrition GmbH, Cuxhaven, Germany) in high-producing Holstein cows during a long-term environmental heat stress period. A total of 62 multiparous lactating Holstein cows were allocated in a completely randomized design to two dietary treatments, namely, basal diet without (control) and basal diet with the supplemental Zn-Met complex (RPZM) at 0.131% of diet DM. Cows in the RPZM group had higher energy-corrected milk (46.71 vs. 52.85 ± 1.72 kg/d for control and RPZM groups, respectively) as well as milk fat and protein concentration (27.28 vs. 32.80 ± 1.82 and 30.13 vs. 31.03 ± 0.25 g/kg for control and RPZM groups, respectively). The Zn-Met complex supplemented cows had lower haptoglobin and IL-1B concentration than the control (267 vs. 240 ± 10.53 mcg/mL and 76.8 vs. 60.0 ± 3.4 ng/L for control and RPZM groups, respectively). RPZM supplementation resulted in better oxidative status, indicated by higher total antioxidant status and lower malondialdehyde concentrations (0.62 vs. 0.68 ± 0.02 mmol/L and 2.01 vs. 1.76 ± 0.15 nmol/L for control and RPZM groups, respectively). Overall, the results from this study showed that RPZM dietary inclusion could maintain milk production and milk composition of animals during periods of heat stress. Enhanced performance of animals upon Zn-Met complex supplementation could be partly due to improved oxidative and immune status.